Preparation and Evaluation of Cefixime Nanocrystals - A. Hussein, Ahmed; Sh. Mahmood, Hasanain (Iraqi Journal of Pharmaceutical Sciences, 2017)
Drug nanocrystals are nanoscopic crystals of the parent compound with dimensions less than 1 Âµm. A decrease in particle size will lead to an increase in effective surface area in the diffusion layer, which, in turn, increases the drug dissolution rate. Drug nanocrystals are one of the most important strategies to enhance the oral bioavailability of hydrophobic drugs.Cefixime is the first member of what is generally termed the third generation orally active cephalosporins. These third generation cephalosporins are distinct from the older Î²-lactam antibiotics in their intensive antibacterial activity against a wide range of gram-negative bacteria.The aim of this study is to prepare nanocrystals of cefixime as a capsules dosage form in order to increase its oral dissolution rate and bioavailability.The cefixime nanocrystals were prepared by solvent/antisolvent precipitation method. Certain amount of drug was dissolved in water miscible solvent (methanol used in this study), then this solution was injected (at certain speed) into water containing stabilizer. Upon injection, precipitation of cefixime nanocrystal will occur immediately; this precipitate is sonicated at 37 ËšC for 30 min. then lyophilized. Powder of nanocrystal was obtained and filled into capsules. The physicochemical interaction between drug and addatives was studied using FTIR, DSC,Results show that the best formula of cefixime nanocrystals prepared by dissolving 20mg/ml of cefixime in methanol, then 5ml was injected at 60ml/hr rate to a 50ml PVP solution as stabilizer in concentration 0.05%, then lyophilized to obtain the cefixime nanocrystal powder. The resulted mean particle size was 9-11 nm and the dissolution rate was significantly higher than that of the raw cefixime powder (p>0.05).Keywords: Cefixime trihydrate, Nanocrystals, Anti-solvent precipitation, PVP, HPMC, Poloxamer 188.